Spatial analysis and urban land use planning with emphasis on hospital site selection, case study: Isfahan city - Soltani, Ali; Balaghi, Rasoul; Rezaei, Meysam; Riyabi, M. Akbari (Bulletin of Geography. Socio-economic Series, 2019)
Providing appropriate and equal health care to various classes of society is among the major issues in social welfare. Optimum spatial distribution and equitable locating of health services is important. Due to high population and density in the metropolis of Isfahan, quantitative and qualitative evaluation of hospitals of the city based on the related standards and regulations seems to be necessary. In this study, a combination of GIS and network analysis was used to evaluate the catchment areas of existing hospitals in Isfahan. The results indicated that existing hospitals covered only 23.91 percent of active urban areas at standard time. To promote fair access for citizens and improve the spatial distribution of hospitals based on the related standards and regulations, valuation of urban land for locating new hospital is necessary. Thus, with effective data collection in the form of layers of information such as transportation network, population density, land use, etc. using GIS and AHP model, the authors categorized urban land in 7 categories from poor to very good for construction of hospitals